Institutionalization оf Financial literacy оf the Adult Population оf Russia - O. V. Kuznetsov; A. V. Ivanov; N. V. Vorovskii; I. S. Shevalkin (Финансы: теория и практика)
The relevance of the article is conditioned by the need to study institutionalization of financial literacy of the adult population, as well as to increase its level due to financial services and products emerging on the market (banking, investment, insurance, pension) and tools for their use. The novelty of this topic is associated with a systematic analysis of the institutionalization processes of financial literacy of the adult population, which makes a significant contribution to implementing national goals and strategic objectives of the development of the Russian Federation, and is also an important consumer of financial services. The aim of the article is a comprehensive scientific study of the institutionalization processes of financial literacy of the adult population. Techniques such as content analysis of references, verification, analysis, statistical and sociological methods (survey), crosstabulation, etc. were employed to analyze the data. Theoretical and methodological principles of institutionalization of financial literacy of the adult population were analyzed. The authors developed a conceptual model of its institutionalization. The study analyzed the state and dynamics of institutionalization of financial literacy of the adult population. The authors formulated the conclusions and recommendations on the sustainable development of institutional entities that contribute to improving the financial literacy of the adult population. The study calls for including the list of target population groups of citizens of retirement and pre-retirement age, as well as persons with disabilities, in the Strategy for Improving Financial Literacy in the Russian Federation in 2017–2023; making arrangements for financial education of the population within the national projects “Digital Economy”, “Education”, “Culture”, “Demography”; supporting the creation of electronic platforms and online panels in educational organizations for systematic financial education of various target groups of the population of the Russian Federation, etc.